Eyebrows, Rajesh Mansion - Ayan Ghosh (2023)
The cantilevered ledge located above the windows is referred to as the eyebrows. Their main purpose is to block direct sunlight and shade the interiors. By using clusters of eyebrows, architects used to accentuate the rhythmic horizontality of buildings, including at Rajesh Mansion.